IMPLEMENTATION OF VORTEX MACHINES IN BAKERY PRODUCTION - SAVCHENKO, MARYNA; RADCHUK, OLEG; KOSHEL, OLENA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Bread production is one of the most essential branches of the food industry, which provides the population with the main food product. The quality of bread, flour confectionery, and products from wheat directly depends on the quality of raw materials, their biological value and production technology, and the equipment used. One of the critical stages in flour preparation is its sifting, which plays a vital role in improving the characteristics of flour and, accordingly, the finished product. The production of food products is accompanied by the generation of waste, which, in any case, enters the environment without proper cleaning, especially in large enterprises with old technologies and equipment. Using such equipment leads to severe illnesses among workers. Currently, liquid waste, a significant pollutant, prevails in food enterprises. Today’s urgent problem is cleaning dusty gases at elevators, flour mills, grain mills, feed mills, granaries, grain dryers, and agricultural enterprises. That’s why, an experimental and theoretical study was conducted to determine the efficiency of flour capture by improved vortex installations. The separation of solid particles from the dusty flour stream was investigated. The overall efficiency of the device with opposing swirling flows is determined. A sieve analysis of flour was carried out. Fractional size samples of dust-dispersed flour particles were obtained. The process of drying wet flour in devices with opposite swirling flows was studied for its further use in flour confectionery products. The prospective use of the proposed vortex dust collector as a drying device has been proven. The conducted experimental and theoretical research on the determination of the efficiency of improved vortex installations, the separation of solid particles from dusty air based on flour, the determination of the overall efficiency, the size of fractions, the sieve analysis of flour, and the study of wet flour for drying in the ACSF were investigated, which is evidence that that the device with the opposite swirling flows is not only for catching various types of dusty food products but also for drying this or that product, which is quite convenient to use.